Capacitación Tecnológica y su influencia en los docentes en tiempo de pandemia en la Unidad Educativa Replica Eugenio Espejo en el periodo lectivo 2021-2022 - Trejo Martínez, Alex Alexis (2022)
In this research work, the purpose is to determine the influence of technological training on teachers in times of pandemic in the Replica Eugenio Espejo Educational Unit in the 2021-2022 school year. The problem raised refers to the difficulties of teachers at moderate levels on the management of technology applied in the virtual classroom, therefore, this situation is worrying, given the demand that teachers develop classes online. In the methodological part, the research design is non-experimental, based on a qualitative approach oriented to a descriptive research level, in the data collection the survey technique was used through the online questionnaire generated in google drive, for it 19 teachers were surveyed; In addition, the frequency tables and pie charts created in Microsoft Excel were applied. Obtaining as a conclusion that the application of ICT is promoting teaching, this situation indicates that the contribution of online technology in classroom processes, which motivates students by teachers in the fulfillment of school tasks and that technological knowledge is fostering better learning of technological tools in education.